Technically it's 2x subtracted by 1 and 8 more than that so:
(2x-1)+8
Answer:
The answer is 1/3
Step-by-step explanation:
Let the events of getting the no. greater than 4 be (>4).
Then,
<em>n</em><em>(</em><em>s</em><em>)</em><em> </em><em>=</em><em> </em><em>6</em>
<em>n</em><em>(</em><em>></em><em>4</em><em>)</em><em> </em><em>=</em><em> </em><em>2</em>
<em>P</em><em>(</em><em>></em><em>4</em><em>)</em><em> </em><em>=</em><em> </em><em>n</em><em>(</em><em>></em><em>4</em><em>)</em><em>/</em><em>n</em><em>(</em><em>s</em><em>)</em>
<em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>=</em><em>2</em><em>/</em><em>6</em>
<em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>=</em><em>1</em><em>/</em><em>3</em>
<em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em>
Answer:
(
n
−
5
)
(
2
n
+
9
)
Step-by-step explanation:
Factor by grouping
Answer:
0
3
Step-by-step explanation:
- x²-3x=0
- x(x-3)=0
- x=0
- x-3=0 ⇒ x=3